Editorial Vol6 no2 - Irene Stevens (Scottish Journal of Residential Child Care)
Changing Lives (Scottish Executive, 2006), otherwise known as the Report of the 21st Century Social Work Review will be the key policy document for social service development and reform in the foreseeable future. The bulk of the report discusses the role of the social worker, and residential child care is not discussed specifically. The authors of the report admitted that it was not within their remit to look in detail at the full range of social care services (Scottish Executive, 2006, p. 7) so there may have been an excuse for the lack of discussion about the role of residential child care workers.